Behavioral Determinants Of Internal Pulmonary Tb Patients Prevention Of Transmission To Families In Work Area Pb Selayang II Medan Puskesmas 2022 - Jujur Baktiar Pandiangan; Kesaktian Manurung; Jasmen Manurung (SEAN Institute, 2023)
Tuberculosis is a direct infectious disease caused by TB germs (Mycobacterium tuberculosis) which is still a large family of the genus Mycobacterium. The most important source of infection is the sputum of smear-positive pulmonary TB patients. Transmission occurs through sputum splashes (droplet infection) when the patient coughs, speaks or spits. Factors that cause the incidence of tuberculosis include age, education, occupation, gender, knowledge, nutritional status, occupancy density and the role of health workers. Behavior is an activity or activity of the organism concerned. Behavior is a person's response or reaction to a stimulus (external stimulus). So, it can be concluded that behavior is the activity and reaction of living things to external stimuli. The type of research used is an analytic study with a cross-sectional study design. In this study, the determinants of the behavior of pulmonary TB patients in preventing transmission to the family were examined using instruments in the form of questionnaires and medical records. This research was conducted in the work area of the PB Selayang II Health Center in Medan City with the reason for choosing the research location because there were pulmonary TB sufferers in the family. The sample used in this study was a total sample of 80 people. The results show that age is associated with a P-value of 0.002, gender is associated with a P-value of 0.000, education is associated with a P-value of 0.004, employment is associated with a P-value of 0.000, nutritional status is associated with a P-value -value of 0.000, Knowledge is associated with a P- value of 0.000, occupancy density is associated with a Pvalueof 0.003, the role of health workers is associated with a P-value of 0.010 and the most dominant factor related is gender with xp (B)106,648.